Buridan’s logic: testability and models - López-Astorga, Miguel (Argumentos - Revista de Filosofia, 2025)
The theory of modality Buridan develops is linked to different propositions. This paper addresses one of those propositions. The aim is to show that, if the operator of necessity included in it is ignored, the proposition allows deriving, within first-order predicate logic, a reduction sentence with the characteristics required in Carnap’s framework. Besides, the paper tries to argue that the mentioned operator of necessity can be understood not only in a technical sense (as modal logic does), but also in the way a naïve individual (without modal logical training) could interpret it. These latter arguments are given from the theory of mental models.